Quality and hygiene of beef burgers in relation to the addition of sodium ascorbate, sodium citrate and sodium acetate. (11th November 2013) - Stella, Simone; Tirloni, Erica; Ripamonti, Barbara; Lamanuzzi, Francesca; Cattaneo, Patrizia
Summary We evaluated the effects of two additive mixtures (sodium ascorbate 1 g kg−1, sodium citrate 1 g kg−1 and sodium acetate 1.75 or 2.5 g kg−1) on the microbiological and physical–chemical characteristics of non‐prepacked beef burgers stored in air at 4 °C or 12 °C for 96 h. Total microbial count reached 7 Log CFU g−1 48 h later in treated samples at 4 °C. The mixture containing the higher acetate concentration led to a smaller increase in Gram‐negatives, in particular Pseudomonas (2 Log of difference towards control samples at 96 h); at 12 °C, a 1.7 Log difference in Enterobacteriaceae was also shown. Total viable basic nitrogen was significantly lower in the treated samples at 12 °C. The addition resulted in pH stabilisation and lower cooking loss and positively influenced the a* index of burgers at 4 °C. Clearly, the use of these mixtures should not be a substitute of good hygienic practices and optimal storage conditions.